1982
DOI: 10.1161/01.res.50.6.775
|View full text |Cite
|
Sign up to set email alerts
|

Phasic coronary blood flow velocity in intramural and epicardial coronary arteries.

Abstract: SUMMARY. Knowledge concerning phasic coronary blood flow is based primarily on measurements obtained from epicardial coronary arteries, which, in part, function as capacitors. If present, epicardial capacitance effects could obscure the dynamic nature of phasic intramyocardial perfusion. To analyze this effect of epicardial capacitance, we simultaneously measured coronary blood flow velocity in an epicardial artery (left anterior descending) and an intramural artery (septal) in openchest, anesthetized dogs. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
1
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(69 citation statements)
references
References 22 publications
6
60
1
2
Order By: Relevance
“…6) followed a similar trend to that in canine data, reported by Chilian and Marcus (14), in which the early systolic flow transient (called "mid-systole" in Ref. 14) accounted for 3.5 vs. Ϫ7.2% of the total area under the flowvelocity curve in the LAD and septal artery, respectively.…”
Section: Model Validationsupporting
confidence: 83%
See 2 more Smart Citations
“…6) followed a similar trend to that in canine data, reported by Chilian and Marcus (14), in which the early systolic flow transient (called "mid-systole" in Ref. 14) accounted for 3.5 vs. Ϫ7.2% of the total area under the flowvelocity curve in the LAD and septal artery, respectively.…”
Section: Model Validationsupporting
confidence: 83%
“…This compares with 3.2 vs. Ϫ1.4% for our simulated adult group data and 4.3 vs. Ϫ0.7% for the newborn group data (both groups P Ͻ 0.001, LAD vs. septal). By contrast, the flow integral percentage during late systole was not different between these sites in Chilian and Marcus (14) or in our simulated adult group data; however, in the newborn group, LAD and septal arteries accounted for 7.9 and 4.9%, respectively (P Ͻ 0.001).…”
Section: Model Validationcontrasting
confidence: 77%
See 1 more Smart Citation
“…It has been well known that during myocardial contraction, the diameter of coronary vessels and velocity of blood flow are altered (3,30), causing a change of shear stress in these vessels, leading to vasodilator responses. Some previous studies have reported that pulsatile flow enhances flow-induced dilation and NO production in the coronary circulation (2,21).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent detailed and elegant experimental studies (3,20,(23)(24)(25) have shown that an increased coronary perfusion pressure during systole is counteracted by a rise in intramyocardial pressure which not only throttles, but actively pumps, blood out of the coronary microcirculation. With ventricular relaxation, perfusion pressure decreases but the accompanying lower extravascular compression results in a prominent diastolic surge of coronary flow.…”
mentioning
confidence: 99%